Tissue-Dependent Tumor Microenvironments and Their Impact on Immunotherapy Responses - Oliver, Amanda J.; Lau, Peter K. H.; Unsworth, Ashleigh S.; Loi, Sherene; Darcy, Phillip K.; Kershaw, Michael H.; Slaney, Clare Y. (Frontiers in Immunology, 2018)
Recent advances in cancer immunology have led to a better understanding on the role of the tumor microenvironment (TME) in tumor initiation, progression and metastasis. Tumors can occur at many sites in the body and co-evolution between malignant tumor cells and non-malignant cells sculpts the TME at these sites. It has become increasingly clear that there are specific differences of the TMEs at different anatomical locations, and these tissue-specific TMEs regulate tumor growth, determine metastatic progression and impact on the outcome of therapy responses. Herein, we review the scientific advances in understanding tissue-specific TMEs, discuss their impact on immunotherapeutic response and assess the current clinical knowledge of these tissues-specific TMEs. A deeper understanding of the tissue-specific TME will help to develop effective immunotherapies against tumors and their metastases and assist in predicting clinical outcomes.